The Seeds for Needs Initiative in Ethiopia: integrating farmer and scientist knowledge - Bioversity International (Bioversity International, 2015)
Bioversity International's 'Seeds for Needs' initiative works with farmers to research how agricultural biodiversity can help minimize the risks associated with climate change. The concept is simple – if farmers have better information and access to a wide range of varieties, they are more able to choose what best suits their conditions and cope with unpredictable weather.